HEALTH AND LAW: OBLIGATION OR FACULTY OF VACCINATION AGAINST COVID 19? - Vieira, Tereza Rodrigues; Ortiz, Bruno Martins Duarte (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
The present work aims to analyze the coronavirus vaccination legal aspects. Aprroach the SARS-CoV-2 origins and its evolution around the world, focusing at the Brazilian territory. Beginning with an analysis of all the State powers and federal entities, ahead of the pandemic impacts. At the end, focus at the vaccination and the health crucial right. The study is based on deductive metodology by bibliographics and database, using the law and the Supreme Court judgements.